Gestión presupuestaria en el Gobierno Autónomo Descentralizado Parroquial Rural La Unión, en el período 2023. - Chávez Mosquera, Kevin Oswaldo (2024)
The Decentralized Autonomous Rural Parish Government of La Union is a public entity dedicated to promote the sustainable development of the parish through projects that benefit the people of the community, which is located in the Babahoyo canton, Province of Los Ríos, homewer, in recent years it has presented various shortcomings in the management of the budget, for this reason the objective of this research is to analyze the budget management in the period 2023: The methodology is based on structural analysis through the application of comparison techniques, interviews and surveys, concluding that form the evidence it was possible to know the distribution and use of the budget for the effectiveness of investments according to the need of the community. Likewise, it is recommended to establish programs that encourage citizen participation and that lead to adequate decision making for an effective management in the allocation of resources.